2017
DOI: 10.1108/jidob-09-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Teaching early reading skills to adult offenders with intellectual disability using computer-delivered instruction

Abstract: Purpose The purpose of this paper is to evaluate the feasibility, and effectiveness, of using Headsprout Early Reading (HER), an online computer program, to teach basic reading skills to adult offenders with mild intellectual disabilities (IDs) in a secure hospital. Design/methodology/approach A single subject pre-post-test design replicated across two participants was used. Two standardized literacy tests were completed at baseline, half way through the intervention, and at the end of the intervention perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…SF-DDARIN Tier 1 activities included three master’s student projects, each extending the evidence base across different populations. O’Sullivan et al (2017) used a single-case pre-post-test design to evaluate the feasibility of using HER ® to teach basic reading skills to adult offenders with mild intellectual disabilities in a forensic hospital. An additional component of this research design was the inclusion of two treatment-as-usual (TAU) control participants who did not complete the programme.…”
Section: Sf-ddarin Tier 1 Activities (Phase 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…SF-DDARIN Tier 1 activities included three master’s student projects, each extending the evidence base across different populations. O’Sullivan et al (2017) used a single-case pre-post-test design to evaluate the feasibility of using HER ® to teach basic reading skills to adult offenders with mild intellectual disabilities in a forensic hospital. An additional component of this research design was the inclusion of two treatment-as-usual (TAU) control participants who did not complete the programme.…”
Section: Sf-ddarin Tier 1 Activities (Phase 1)mentioning
confidence: 99%
“…The aim was to evaluate the feasibility of teaching adults with learning disabilities to read using HER ® mediated by support workers or family carers (Moody et al , 2022). The research proposal built upon the Tier 1 O’Sullivan et al (2017) study and the Tier 2 adult reading survey and used the HER ® support manual funded by the SF-DDARIN. Thirty-six participants were recruited and randomised into an intervention group (19 participants) and a TAU group (17 participants).…”
Section: Sf-ddarin Tier 3 Activities (Phases 2/3)mentioning
confidence: 99%
“…All students regardless of age used the same program in which cartoon characters appear in the online episodes. This was considered appropriate as other research had found no negative aspects to the child-friendly design of HER when it was implemented with older teenagers (Tyler et al, 2015b) and with adults (O'Sullivan et al, 2017) with ID.…”
Section: Setting and Participantsmentioning
confidence: 99%